2016
DOI: 10.1007/s10096-016-2639-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of Clostridium difficile in the paediatric and neonatal gut — a narrative review

Abstract: Clostridium difficile is an important nosocomial pathogen in adults. Its significance in children is less well defined, but cases of C. difficile infection (CDI) appear to be increasingly prevalent in paediatric patients. This review aims to summarize reported Clostridium difficile carriage rates across children of different age groups, appraise the relationship between CDI and factors such as method of delivery, type of infant feed, antibiotic use, and co-morbidities, and review factors affecting the gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 104 publications
4
45
5
4
Order By: Relevance
“…However, these findings were not significant in our study. Also, similarly to other studies [6, 7, 14, 21], in-hospital C. difficile colonization was not associated with the development of NEC in our study. This is an interesting finding as a recent in vivo study in mice described that neonatal acquisition of Clostridium spp.…”
Section: Discussionsupporting
confidence: 72%
“…However, these findings were not significant in our study. Also, similarly to other studies [6, 7, 14, 21], in-hospital C. difficile colonization was not associated with the development of NEC in our study. This is an interesting finding as a recent in vivo study in mice described that neonatal acquisition of Clostridium spp.…”
Section: Discussionsupporting
confidence: 72%
“…A meta-analysis of studies examining pediatric C. difficile epidemiology reported an asymptomatic colonization rate of 15% for children older than 1 year of age, with the prevalence reduced to 5% in those older than 2 years of age (117). One explanation for the reduction in colonization rates after infancy is that, by 12 months, the distribution of gut flora begins to closely resemble that of a healthy adult, providing a colonization resistance effect.…”
Section: Children (2 To 16 Years)mentioning
confidence: 99%
“…Asymptomatic colonization with C. difficile is common in infants; in fact, it is estimated that up to 21 to 48% of infants are asymptomatically colonized with C. difficile (62). Although it is not known why colonized infants generally do not develop disease, it has been suggested that they could be protected by a lack of functional toxin receptors or by antibodies in breast milk (63). Asymptomatic colonization can also occur in adults (62), but old age is a risk factor for the development of symptomatic CDI (64)(65)(66).…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%